Pengamatan terhadap pembiakan cladocera (Macrothrix sp.) dan phytoplankton secara eksitu: Observation of culturing cladocera (Macrothrix sp.) and phytoplankton under laboratory condition - Hamdhani Hamdhani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
Zooplankton plays important role in food chain system within fresh water ecosystem. In the trophic level it acts as bridging energy from phytoplankton to fish juvenile. Meanwhile research on this plankton is considerably lacking. This study is aimed to test culturing cladocera in the laboratory. Cladocera and phytoplankton were collected from Lutan Lake-Palangkaraya and the transported to the laboratory. Three fish water tank were used to culture cladocera for 5-week testing. The results indicate that there was a negative relationship between average numbers of cladocera dan phytoplankton during culturing period. Two-week culturing period was identified as the most optimal period for culturing cladocera under laboratory condition.